Film and national culture in Namibia: a study and analysis of how the films 100 Bucks and Try have contributed to the creation of post-colonial identity and national culture in independent Namibia - Katjavivi, Perivi John (Centre for Film and Media Studies, 2017)
I wish to present a study of the different literature regarding national culture, African cinema and postcolonial identity and explore how it relates to local cinema in Namibia. How have Namibian films contributed to this debate? The films 100 Bucks and Try contributed to the creation of postcolonial identity and national culture in independent Namibia. This dissertation will focus primarily on the aesthetics, themes and stories produced in Namibia since 2000 as well as how our storytelling and funding models can learn from other industries throughout the world. I will undertake an examination of past works and writings on the topic of national culture in post colonial African states, nationalism and African identity.